DOI: 10.24124/2004/bpgub322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of root deformation on growth and susceptibility of lodgepole pine to attack by the Warren root collar weevil.

Abstract: The author has granted a non exclusive license allowing Library and Archives Canada to reproduce, publish, archive, preserve, conserve, communicate to the public by telecommunication or on the Internet, loan, distribute and sell theses worldwide, for commercial or non commercial purposes, in microform, paper, electronic and/or any other formats. AVIS: L'auteur a accordé une licence non exclusive permettant à la Bibliothèque et Archives Canada de reproduire, publier, archiver, sauvegarder, conserver, transmettr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Second, projected increases in drought stress 2 place these forests at risk for future mortality, and management treatments that impose additional stress, such as nutrient limitations, may compound this risk. High levels of mortality due to recent summer droughts (Maclauchlan et al 2004), dothistroma needle blight (Woods et al 2005), Warren's root-collar weevil (Robert 2004), and armillaria root disease (Simard et al 2005) have already been detected in well-established lodgepole pine plantations.…”
Section: Discussionmentioning
confidence: 97%
“…Second, projected increases in drought stress 2 place these forests at risk for future mortality, and management treatments that impose additional stress, such as nutrient limitations, may compound this risk. High levels of mortality due to recent summer droughts (Maclauchlan et al 2004), dothistroma needle blight (Woods et al 2005), Warren's root-collar weevil (Robert 2004), and armillaria root disease (Simard et al 2005) have already been detected in well-established lodgepole pine plantations.…”
Section: Discussionmentioning
confidence: 97%
“…If planted at sufficiently high densities, mortality will not normally be high enough to threaten a stand. Planted trees with severe root fault (e.g., so called J-root caused by improper planting), however, appear to be more likely to suffer mortality than naturally regenerated trees, even though there is no difference in susceptibility to attack (Robert, 2004). Therefore, natural regeneration may be preferable to planting in areas with high weevil populations.…”
Section: Discussionmentioning
confidence: 98%
“…However, we found that it was the rootstock diameter relative to the scion diameter that was significant, indicating some interaction between scion and rootstock. Hence, we contend that if physiological processes are compromised, for example by grafting or root dysfunction ( Robert, 2004 ), susceptibility to insect pests may be affected, even if shoot growth appears to be unaffected. Further study of how tree physiology is affected by grafting is needed to fully understand how trees respond to grafting, and whether trees with no apparent symptoms of graft incompatibility are compromised in any way.…”
Section: Discussionmentioning
confidence: 99%
“…Such physiological constraints (e.g. due to grafting or root dysfunction in container-grown or improperly planted seedlings) ( Robert, 2004 ) could potentially affect susceptibility to phloeophagous insects.…”
Section: Discussionmentioning
confidence: 99%